2020
DOI: 10.1137/19m1248327
|View full text |Cite
|
Sign up to set email alerts
|

Data Assimilation in Large Prandtl Rayleigh--Bénard Convection from Thermal Measurements

Abstract: This work applies a continuous data assimilation scheme-a particular framework for reconciling sparse and potentially noisy observations to a mathematical model-to Rayleigh-Bénard convection at infinite or large Prandtl numbers using only the temperature field as observables. These Prandtl numbers are applicable to the earth's mantle and to gases under high pressure. We rigorously identify conditions that guarantee synchronization between the observed system and the model, then confirm the applicability of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…In the context of NWP, different formulations of nudging have been used to study the state estimation problem using finite-dimensional dynamical systems and weather models [25,[29][30][31], and for boundary condition matching [32][33][34]. In the context of turbulence, for the cases of a two-dimensional Navier-Stokes equation (NSE) [35][36][37][38], the three-dimensional Navier-Stokes α model [39], and Rayleigh-Bénard convection [40,41], it has been rigorously proven that given a sufficient amount of input data, a nudged field will eventually synchronize with its nudging field. Indeed, both DA [42] and nudging can be framed as a synchronization problem; see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of NWP, different formulations of nudging have been used to study the state estimation problem using finite-dimensional dynamical systems and weather models [25,[29][30][31], and for boundary condition matching [32][33][34]. In the context of turbulence, for the cases of a two-dimensional Navier-Stokes equation (NSE) [35][36][37][38], the three-dimensional Navier-Stokes α model [39], and Rayleigh-Bénard convection [40,41], it has been rigorously proven that given a sufficient amount of input data, a nudged field will eventually synchronize with its nudging field. Indeed, both DA [42] and nudging can be framed as a synchronization problem; see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…By adapting a data assimilation scheme for Bénard convection from Farhat et al (2016Farhat et al ( , 2020 present a data assimilation scheme for noisy temperature measurements of large to infinite Prandtl number RBC flows based on Newtonian relaxation. Evaluating their data assimilation scheme analytically and by means of two-dimensional direct numerical simulations of moderately turbulent flow, Farhat et al (2020) establish that their scheme successfully assimilates temperature fields if the number of projected modes and the relaxation parameter relative to the Rayleigh number are large enough. More often than not, only the measured velocity fields are available, whereas pressure, temperature, or other scaler fields are also required to fully characterise the flow phenomenology.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies 13,14 showed that the conjectures is true in simple systems, but also presented numerical evidence to the contrary. In the past few years the conjecture has been studied in different models, such as in a 3D Planetary Geostrophic model 15 , a Rayleigh-Bénard flow in the infinite Prandtl number limit 16 , and a Rayleigh-Bénard flow in the non-turbulent regime 17 . The first two studies were successful in reconstructing the whole state out of thermal measurements, but the third study struggled to do so when the prior on the velocity field was not set correctly.…”
Section: Introductionmentioning
confidence: 99%